Modernisation of Laboratory Based Instructions - Tandon, Vikas (Journal of Engineering Education Transformations, 1993)
In the present day scenario of technical 'education, it has been observed that Laboratory based instructions play an important role in making the process of teaching learning more effective and challenging. Experience and research have - shown that many of the Â·instructional objectives related to skill learning, concept learning, principle learning and problem-solving can be achieved through laboratory work rather than classroom teaching. For an educational system to be successful, laboratories must be well equipped not only with the latest equipment but also its staff should be well acquainted with their operation and maintenance. This paper deals with the different aims and objectives of laboratory based instructions including its planning and present status. The paper describes certain methods by which laboratory work can bring about excellence in technical education.